Hepcidin regulation in Malaria - Spottiswoode, N (2015)
Epidemiological observations have linked increased host iron with malaria susceptibility. At the same time, blood-stage malaria infection is associated with potentially life-threatening anemia. To improve our understanding of these relationships, this work presents an examination of the mechanisms controlling the upregulation of the hormone hepcidin, the master regulator of iron metabolism, in malaria infection. Chapter 2 presents data from a mouse model of malaria infection which indicate that hepcidin upregulation in malaria infection is associated with increased activity of the sons of mothers against decapentaplegic (Smad) signaling pathway. Although the canonical Smad pathway activators, bone morphogenetic proteins (Bmp) are not increased at the message level following infection, activin B, which has been recently shown to increase hepcidin through the Smad signaling pathway in conditions of inflammation and infection, is upregulated in the livers of malaria-infected mice. Chapter 3 shows that both activin B and the closely related protein activin A upregulate hepcidin in vitro and in vivo. Chapter 3 also explores the effects of the activin-binding protein follistatin in both systems and in the same malaria-infected mouse model as presented in Chapter 2. The work presented in Chapter 4 extends these studies to human infections by demonstrating that activin A protein co-increases with hepcidin in human serum during malaria infection. Taken together, these findings are consistent with a novel role for activin proteins in controlling hepcidin upregulation in the context of malaria infection. This work may form a basis for the development of novel therapeutics that speed recovery from malarial anemia by inhibiting activins’ actions. Chapter 5 examines the role of infected red blood cell-derived microparticles in the initial recognition of a P. falciparum malaria infection, and subsequent hepcidin upregulation. Microparticles stimulate production of cytokines from peripheral blood mononuclear cells (PBMC), which also upregulate activin A message in response to both microparticles and whole infected red blood cells. These data are consistent with a model in which malaria-derived stimuli such as microparticles trigger the systemic release of activin proteins, which then act on the liver to upregulate hepcidin. Evidence has shown that cytokine levels at birth are related to malaria risk. In Chapter 6, hepcidin is measured in cord blood samples from participants in a large-scale clinical study in a malaria-endemic area, and shown to be elevated in cord blood from neonates with a clinical history of placental malaria. Cord blood hepcidin is also compared to birth levels of iron markers and other cytokines, and future clinical outcomes. Finally, the contributions of DNA methylation levels to cord hepcidin and cytokine levels are assessed by comparison of CpG methylation, at sites in genes encoding hepcidin and cytokines, to the serum concentrations of the genes’ protein products. Several intriguing associations are noted which indicate a possible novel role for DNA methylation in the determination of birth cytokine and hepcidin levels. Chapter 7 synthesizes the data presented in this thesis, interprets the possible significance of the major findings, and offers suggestions for future work.